Experiences of Women with the Labour and Delivery Care Received at Mzimba District Hospital, Malawi - Julia Tanangachi Nyirongo; Angella Chimwaza (International Journal of Women's Health Nursing And Practices, 2024)
Aim: The aim of the study was to explore the perceptions of women on the care that they received during normal labour and delivery at Mzimba District Hospital, Malawi. Specific Objectives: To evaluate the aspects of physical care that was rendered to women during labour and delivery, evaluate the psychological care that was rendered to women throughout labour and delivery, assess the perception of women on the attitudes of midwives during the provision of labour and delivery care and review participants’ files for documentation of labour and delivery care. Methods: The study was of explorative and descriptive design that utilized qualitative methods. The study was conducted at Mzimba District Hospital in the postnatal ward in Malawi. The sample was drawn from women who had spontaneous vertex deliveries with no complications for both the mother and baby. A purposive sampling was used to select the 15 participants for the study and included women who laboured from 4 to 5 cm and delivered without complications at the institution. Data Analysis: Descriptive statistics were computed for demographic data and qualitative data were analysed manually using thematic content analysis. Results: Results revealed that women who participated in the study received inadequate intrapartum care and the major results from the study were inadequate history taking, inadequate physical assessment, inadequate giving of information, lack of pain relief measures, lack of food and fluid intake and output, lack of use of various positions, lack of mobility during labour and delivery, lack of birth companion, poorly managed anxiety, dissatisfaction with midwives’ attitudes, and inadequate documentation of labour and delivery care.
Keywords: Labour and delivery; intrapartum care; labouring women and perception; spontaneous vertex delivery